2016
DOI: 10.1007/s11676-016-0306-2
|View full text |Cite
|
Sign up to set email alerts
|

Flotation techniques to improve viability of Juniperus polycarpos seed lots

Abstract: The germination of freshly collected Juniperus polycarpos (K. Koch) seeds is very low and attributed to the large proportion of nonviable seeds in the seed lots. Thus, the aim of this study was to improve seed lot quality by removing nonviable seeds using two flotation techniques: incubation-drying-separation (IDS) and modified specific gravity (MSG) separation. We examined different IDS conditions (the specific incubation time, subsequent drying time and sorting media) for effectively sorting out nonviable se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…Seed quality has been an important factor in achieving high germination and uniform growth rates in agricultural crops (Hussain et al 2018). Seed quality depends on many factors including seed physiology and chemical composition (Copeland and McDonald 2001). In particular, germination and vigor are largely determined by the amount of mineral nutrients, carbohydrates, proteins, and lipids in seeds (Andreasen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Seed quality has been an important factor in achieving high germination and uniform growth rates in agricultural crops (Hussain et al 2018). Seed quality depends on many factors including seed physiology and chemical composition (Copeland and McDonald 2001). In particular, germination and vigor are largely determined by the amount of mineral nutrients, carbohydrates, proteins, and lipids in seeds (Andreasen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Five hundred and fifty (550) ripe fruits of Irvingia gabonensis procured from the Department of Forestry of Anambra State Ministry of Environment were de-pulped manually with knife to scrap off the mesocarp. The obtained seeds were subjected to viability test by flotation method [22] and five hundred and forty three (543) that passed the test were sun dried at the screen house temperature of 25-30°C for 24 hours. Seventy (70) seeds were then sown in seven open wooden germination beds measuring 2.5 m x 1.5 m x 0.3 m filled with the 6 different soil amendments and the control of unamended top soil.…”
Section: Fruit Preparation and Germinationmentioning
confidence: 99%
“…Rugemalila et al (2017) found that 33% of A. tortilis and 61% of A. robusta seeds was infested in 2014, which can severely affect natural regeneration of these species. In this regard, Daneshvar et al (2017) found that 75 to 82% of J. polycarpos seeds was empty and insect-infested, but they didn't go deep in the case.…”
Section: Introductionmentioning
confidence: 96%